The Role of Emotional Design in E-Learning Applications on Student Learning Engagement - Putri, Atiqah Zayda (Acta Psychologia, 2025)
The increasing use of e-learning platforms has reshaped the educational experience, emphasizing the need to maintain student engagement in digital learning environments. This study explores the role of emotional design in influencing students’ motivation, participation, and cognitive engagement in e-learning applications. Guided by the Cognitive-Affective Theory of Learning with Media (Moreno & Mayer, 2007), Emotional Design Theory (Norman, 2004), and Self-Determination Theory (Deci & Ryan, 2000), the research investigates how aesthetic, interactive, and emotionally responsive design elements enhance the learning process. This study employs a quantitative research design with a correlational approach to examine the relationship between emotional design elements in e-learning applications and student learning engagement. The results reveal that emotional design significantly affects learners’ engagement by fostering positive emotions, motivation, and sustained participation. Visually appealing layouts, interactive feedback, and personalized features were found to reduce cognitive fatigue and increase learners’ sense of enjoyment and competence. These findings are consistent with earlier studies (e.g., Um et al., 2012; Plass et al., 2014) that emphasized the importance of affective factors in multimedia learning. However, this study extends existing literature by highlighting the value of adaptive emotional feedback and emotionally intelligent interface design that dynamically responds to learners’ needs and emotional states. The implications of this study underscore the importance of integrating emotional intelligence principles into e-learning design to promote a more holistic and human-centered educational experience. Educators and developers are encouraged to design digital learning environments that not only deliver information but also connect with learners emotionally, thereby enhancing motivation, attention, and long-term engagement. Emotional design, therefore, emerges as a key determinant of effective and meaningful learning in the digital age.